2020
DOI: 10.3390/rs12101542
|View full text |Cite
|
Sign up to set email alerts
|

3D Point Cloud Analysis for Damage Detection on Hyperboloid Cooling Tower Shells

Abstract: The safe operation and maintenance of the appropriate strength of hyperboloid cooling towers require special supervision and a maintenance plan that takes into consideration the condition of the structure. With three series of terrestrial laser scanning data, the paper presents an automatic inspection system for reinforced concrete cooling tower shells that ensures detection and measurement of damage together with the verification of the quality and durability of surface repairs as required by industry standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…The result of this research showed realistic quantification, which encouraged the bridge engineers to better quantify bridge damages using TLS. Mass loss damage can also be generated due to spalling and scaling in concrete surfaces [109][110][111]. In this regard, Mizoguchi et al [109] proposed an effective method based on region growing algorithm for quantitative analysis of the scaling on damaged surfaces of concrete structures using laser scanning data.…”
Section: Mass Loss Scaling and Spallingmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of this research showed realistic quantification, which encouraged the bridge engineers to better quantify bridge damages using TLS. Mass loss damage can also be generated due to spalling and scaling in concrete surfaces [109][110][111]. In this regard, Mizoguchi et al [109] proposed an effective method based on region growing algorithm for quantitative analysis of the scaling on damaged surfaces of concrete structures using laser scanning data.…”
Section: Mass Loss Scaling and Spallingmentioning
confidence: 99%
“…Similarly, a recent technique for detecting such damages presented by Kim et al [112] allows engineers to specify the location of surface damages and quantify the spalling defects. The results of this research indicated that the proposed technique is applicable Mass loss damage can also be generated due to spalling and scaling in concrete surfaces [109][110][111]. In this regard, Mizoguchi et al [109] proposed an effective method based on region growing algorithm for quantitative analysis of the scaling on damaged surfaces of concrete structures using laser scanning data.…”
Section: Mass Loss Scaling and Spallingmentioning
confidence: 99%
“…TLS is a new sensing technology that uses laser reflection signals to measure the distance between the target and the scanner by emitting and receiving a laser beam and calculates the threedimensional coordinates of all sampled points on the target surface from the attitude angle of the scanner when the laser beam is emitted. Compared with traditional remote sensing technology, three-dimensional laser scanning technology has the ability to obtain accurate, fast, and real-time data on the true shape of the surface of the target object because it is based on the active measurement method, does not rely on visible light, has a more flexible operation mode [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In situ, field tests and measurements are commonly utilized for the purpose of non-destructive testing. In [7] TLS automatic inspection system, enabling detection and measurement of damage together with the verification of the quality and durability of surface repairs, as required by industry standards, is presented. A new approach for assessing the dimensional accuracy and structural performance of spatial structure elements, using three dimensional (3D) laser scanning, has been shown in [8].…”
Section: Introduction and Research Backgroundmentioning
confidence: 99%